Implementation of Life Cycle Assessment on Tempeh Production at “Tempe Ibu Sujati”, Yogyakarta - Wahyu Supartono; Alfio Fiwa S; Indah Sinthia D; Kartika Saptari P; Muhammad Farhan S; Muhammad Rizky R (Agroindustrial Journal, 2021)
Tempeh is one of Indonesian traditional food that have been favored by the locals for centuries. Tempeh has a life cycle from the supply of raw materials, production processes, packaging and transportation that have a potential impact on the environment. In this study Life Cycle Assessment (LCA) is used as a tool to evaluate the environmental impact on Global Warming Potential (GMP). The LCA study will be conducted in tempeh industry “Ibu Sujati” located at Pandean Street, Umbulharjo, Yogyakarta. The LCA study will be focused on the energy consumption in production process, including the raw material transportation . The result showed the boiling process which part of production process has the largest GWP value that equals to 0.488388 kg CO2-eq which contributes 78.79% of the total GWP in the system boundaries.